2020
DOI: 10.1094/pdis-10-19-2237-re
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of the SoyNAM Parents to Seed and Root Rot Caused by Four Pythium Species

Abstract: Some Pythium spp. cause damping off and root rot in soybeans and other crop species. One of the most effective management tools to reduce disease is host resistance; however, little is known about resistance in soybean to Pythium spp. The soybean nested associated mapping (SoyNAM) parent lines are a set of germplasms that were crossed to a single hub parent to create recombinant inbred line populations for the purpose of mapping agronomic traits. The SoyNAM parents were screened for resistance to Pyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Archer is a cultivar that was identified with resistance to G. ultimum, G. irregulare, P. aphanidermatum and P. vexans (Bates et al, 2008). Additionally, Maverick is a soybean cultivar characterized as resistant to P. lutarium, P. oopapillum, P. sylvaticum and P. torulosum (Lerch-Olson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Archer is a cultivar that was identified with resistance to G. ultimum, G. irregulare, P. aphanidermatum and P. vexans (Bates et al, 2008). Additionally, Maverick is a soybean cultivar characterized as resistant to P. lutarium, P. oopapillum, P. sylvaticum and P. torulosum (Lerch-Olson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have measured resistance toward different Pythium species (Rod et al, 2018;Lerch-Olson et al, 2020) and have identified QDRL, mostly minor, in RIL populations of soybean (Ellis et al, 2013;Stasko et al, 2016;Urrea et al, 2017;Klepadlo et al, 2019;Lin et al, 2018Lin et al, , 2020Scott et al, 2019). Almost all of the studies have shown partial resistance aside from one study by Rosso et al (2008) showing monogenic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…AGERM was calculated as the number of germinated seeds that were inoculated/number of germinated seeds that were non-inoculated. There was a strong negative correlation between ROTS and AGERM, which was also seen in Lerch-Olson et al (2020). Therefore, AGERM data were not used for identifying QDRL.…”
Section: Disease Screeningmentioning
confidence: 99%
See 2 more Smart Citations